2014
DOI: 10.4172/2168-9458.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Openness and Macroeconomic Volatility: Do Development Factors Drive Such Ambiguous Results?

Abstract: The 2008 financial crisis proved the "Great Moderation" (a period when it was believed that policymakers had successfully smoothed macroeconomic fluctuations) to be transitory. Understanding a country's degree of susceptibility to these fluctuations is crucial to investors but previous studies have shown that increasing trade and financial openness can have ambiguous effects. This paper examines a set of 11 countries individually, before the financial crisis, modeling variability in output, consumption, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This result was replicated for GDP growth rate in our pool OLS estimation, it shows that trade openness negatively affects volatility of term-of-trade adjusted output growth and volatility of GNP (results are available on request). While some theoretical and empirical works have shown that trade liberalisation leads to greater output volatility (Ahmed & Suardi, 2009; Drion, 2011; Easterly et al, 2001; Krugman, 1993; Razin & Rose, 1992), due to the facts that it exposes the economy to external risks, other works by (Calderón & Schmidt-Hebbel, 2008; Hegerty, 2014; Kim, 2007; Moore & Walkes, 2007) argued that trade openness may enable a country to expand and diversify its export sector and by varying its export industry, a country reduces its dependency on a small number of products or trading partners and also reduce a country’s exposure to domestic risk, which may however leads to a lower growth volatility.…”
Section: Resultsmentioning
confidence: 99%
“…This result was replicated for GDP growth rate in our pool OLS estimation, it shows that trade openness negatively affects volatility of term-of-trade adjusted output growth and volatility of GNP (results are available on request). While some theoretical and empirical works have shown that trade liberalisation leads to greater output volatility (Ahmed & Suardi, 2009; Drion, 2011; Easterly et al, 2001; Krugman, 1993; Razin & Rose, 1992), due to the facts that it exposes the economy to external risks, other works by (Calderón & Schmidt-Hebbel, 2008; Hegerty, 2014; Kim, 2007; Moore & Walkes, 2007) argued that trade openness may enable a country to expand and diversify its export sector and by varying its export industry, a country reduces its dependency on a small number of products or trading partners and also reduce a country’s exposure to domestic risk, which may however leads to a lower growth volatility.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies emphasises on the catalytic effects of developmental factors on the financial integration-macroeconomic volatility nexus. Consumption growth volatility increases with the level of financial integration in countries with less developed financial markets but tend to decrease in more developed financial markets (Eozenou, 2008), whilst others found no effect on consumption except for a negative effect on output volatility in countries with high degree of financial openness, law and order and initial level of capita compared to other countries (Hegerty, 2014). Recent studies tend to give credence to previous empirical work.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The macroeconomic implications of such type of integration are relevant for developing countries where gradual approach is a favourable policy option. The literature tend to emphasise on deep integration (Kose et al, 2003;Kalemli-Ozcan and Sorensen, 2010;Hegerty, 2014), neglecting the implications of low levels of integration. The successful promotion of full-fledged financial integration requires an understanding of the transitional effects of implementing the policy.…”
Section: Jed 222mentioning
confidence: 99%
“…Furthermore, volatility may also lead to lower growth (Ramey and Ramey, 1995), particularly in the case of poor countries . Hnatkovska and Loayza (2005) for example, estimate that a one standard-deviation increase in macroeconomic volatility results in an average loss of 1.3 percentage points in annual per capita GDP growth.…”
Section: The Downsides Of Volatilitymentioning
confidence: 99%